Mechatronics book series system design and signal processing (V1) - Abdul Muthalif, Asan Gani (IIUM Press, 2011)
This book is part of the Department of Mechatronics Engineering’s continuous effort to exchange information, ideas share knowledge on the frontiers of Mechatronics and its application. The diverse applications of Mechatronics are all crucial to the commercial production for sustainable growth, economic and industrial development of a nation.